Application of calcium carbonate (CaCo3) at different time intervals on the growth of freshwater lobster (Cherax quadricarinatus) - Hastuti, Yuni Puji; Nurussalam, Wildan; Supriyono, Eddy; N Hutomo; Lesmana, Dudi (Universitas Djuanda, 2024)
Freshwater lobsters are one of the crustacean commodities that have started to be developed through cultivation. Besides having high nutritional value, freshwater lobsters have a stable sales value or price throughout the year. Freshwater lobster is a crustacean commodity that is not easily stressed or easily attacked by disease. The availability of calcium is essential for lobster growth, especially the formation of its shell. This research aims to determine the effectiveness of adding calcium carbonate at different time intervals by adding 150 mg/L CaCO3 lime. The study was conducted from June to July 2020 at the Aquaculture Environmental Laboratory, Bogor Agricultural Institute. The research used a Completely Randomized Design (CRD) with five treatments and three replications. The treatment used was K+ and K-, and the time interval for adding CaCO3 was once every five days, once every ten days, and once every 15 days. The aquarium measures 100 x 50 x 51 cm with a water height of 21 cm. The lobster used measures 1.5 cm. The research results after statistical testing showed that aquarium A1 (addition of CaCO3 every five days) experienced an increase in length of 0.67 cm. Weight of 0.67 g, B1 (addition of CaCO3 every ten days) experienced an increase in length of 0.87 cm and weight of 0.78 g, C1 (addition of CaCO3 every 15 days) experienced an increase in length of 0.97 cm and weight of 0.98 g, K+1 experienced an increase in length of 1.05 cm and weight of 1.06 gr, K-1 experienced an increase in length of 0.46 cm and weight of 0.45 g.